Measuring Factors Affecting Customer Satisfaction, Loyalty, And Trust Within Islamic Banks In Riau, Indonesia - Wali Saputra (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita)
This scholarly investigation analyses the determinants that affect customer satisfaction, loyalty, and trust within Islamic banking. The data source used in this study is primary data, which is obtained through the provision of structured questionnaires. The study population encompasses customers of Islamic banking institutions in Riau, Indonesia. The sampling technique employed is simple random sampling. The sample size was determined using the Slovin approach, resulting in a sample of 204 respondents. This study is quantitative, and an explanatory survey was analyzed using the SEM-PLS technique. The study outcomes indicate that service performance, digital banking application service quality, and customer relationship management positively influence customer satisfaction. In contrast, digital banking transformation does not affect customer satisfaction. Furthermore, customer satisfaction has a positive effect on customer loyalty and trust. Subsequently, customer satisfaction can mediate the influence of service performance, the quality of digital banking application services, and customer relationship management on customer loyalty and trust. In contrast, customer satisfaction cannot mediate the influence of digital banking transformation on customer loyalty and trust. Theoretically, this study contributes to the advancement of marketing theory and becomes a reference for further research. Practically, it can be a reference for Islamic banks to improve their performance regarding customer satisfaction, loyalty, and trust.